Anemia and thrombocytopenia as initial symptoms of occult breast cancer with bone marrow metastasis: A case report. Issue 45 (November 2017) - Liu, Lulu; Zhang, Jingjing; Chen, Mingtai; Ren, Saisai; Liu, Haihui; Zhang, Hao
Abstract: Rationale: Occult breast cancer (OBC) is a rare type of breast cancer without any symptoms in the breast and is often presented with initial symptoms of axillary lymph node metastasis or other metastases. The low incidence rates of OBC make it a great challenge to diagnose and cure. Patient concerns: Our case was a 58-year-old female affected by dizziness and fatigue for nearly a month. Blood tests revealed anemia and thrombocytopenia, and pathological results of a bone marrow biopsy confirmed the metastatic carcinoma. Diagnoses: It was diagnosed as an OBC based on the positive immunohistochemical staining of cytokeratin (CK) and gross cystic disease fluid protein-15 (GCDFP-15). Interventions: Doctor advised her to check whether the bone metastases existed in order to choose an appropriate treatment. It is highly regrettable that the patient gave up all treatments and left the hospital. Outcomes: Recently, we conducted a telephone follow-up and received that the patient only took tramadol and other painkilling drugs to alleviate the pain caused by cancer. Lessons: The current case inferred that symptoms of anemia and thrombocytopenia should not be ignored for the diagnosis of OBC, and bone marrow biopsy is useful in reducing the rates of misdiagnosis and missed diagnosis of OBC.